2022
DOI: 10.3389/fenvs.2022.834577
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Antibiotic Resistance From Municipal Secondary Effluents by Ozone-Activated Carbon Filtration

Abstract: At wastewater treatment plants (WWTPs), additional steps are introduced for removal of organic micropollutants (OMPs) from the treated effluents, especially pharmaceutical residues. At the same time, a new concern is emerging: antibiotic resistance (AR). This research studied the effect of ozonation, coagulation and granular activated carbon (GAC) filtration applied as tertiary treatment for the removal of OMPs and nutrients, on AR removal. Bacterial culture methods in selective media were used to screen for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In addition, Alexander et al [110] observed the increase of vanA and bla VIM in abundance with surviving bacteria by 4-and 7-fold after ozonation treatment in a pilot scale ozone system. Increasing the ozone dose enhances the ARB removal efficiency [69,70,107]. However, Zheng et al [85] observed that increasing the ozone dose did not contribute to a significantly higher ARGs removal efficiency.…”
Section: Ozonationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Alexander et al [110] observed the increase of vanA and bla VIM in abundance with surviving bacteria by 4-and 7-fold after ozonation treatment in a pilot scale ozone system. Increasing the ozone dose enhances the ARB removal efficiency [69,70,107]. However, Zheng et al [85] observed that increasing the ozone dose did not contribute to a significantly higher ARGs removal efficiency.…”
Section: Ozonationmentioning
confidence: 99%
“…Activated carbon is often used for the adsorption of various pollutants from wastewater such as organic compounds, heavy metals, and pharmaceutical products [67,68]. Activated carbon can be used for the adsorption of antibiotics, ARGs, and ARB found in wastewater [69]. However, ARB and ARGs removal has not yet been widely studied.…”
Section: Granular Activated Carbon (Gac)mentioning
confidence: 99%
See 1 more Smart Citation
“…Ozone can play a role in medicine [34,35] as well as in other areas due to its antibacterial properties and the continued spread of the phenomenon of antibiotic resistance [36][37][38], that is, the inability of antibiotics to effectively fight infections and bacteria, a phenomenon defined by the excessive and often inappropriate use of antibiotics as for people as well as for animals.…”
Section: Antibacterial Propertiesmentioning
confidence: 99%